Inclusão de alunos com Transtorno do Espectro Autista (TEA) na escola regular: uma análise de teses e dissertações produzidas no Brasil de 2012 a 2020 - Bonfim, Jozinalva Oliveira Castelo Branco (Universidade do Vale do Rio dos Sinos, 2021)
Considering inclusion as a process that has no end to be achieved and a which is also a right to all those who, throughout history, have been segregated and excluded from society and school, this piece of research brings as an object of study the inclusion of students with Autism Spectrum Disorder. The goal is to analyze and problematize how researchers, in their dissertations and theses, address and discuss the inclusion of students with Autism Spectrum Disorder in regular school. This is a documentary analysis research, which elected, as a methodological path, the mapping and selection of dissertations and theses developed and published in Brazil, in the period from 2012 to 2020, highlighting as a criterion pieces of research that discussed school inclusion of children with Autism Spectrum Disorder in regular school. I analyzed 11 dissertations and theses and highlighted enunciative recurrences that pointed to socialization as a curricular crossing that dims other types of learning that should be promoted by the school for students with Autism Spectrum Disorder. Faced with such recurrence, socialization was problematized as a type of crossing that ends up determining and reducing the function of the school. The enunciative set derived from the research materials was termed socialization ad aeternum. I argued, while concluding about the purpose of sending children with Autism Spectrum Disorder to regular school, that it does not challenge individuals to differentiated learning and it justifies the importance of school only for socialization, a type of socialization that is never concluded, keeping the student with Autism Spectrum Disorder dependent on the school.
Keywords: Inclusão; Transtorno do Espectro Autista; Inclusão escolar; Socialização; Inclusion; Autism Spectrum Disorder; School inclusion; Socialization; ACCNPQ::Ciências Humanas::Educação